Factors Influencing the Preparation for Elderly of Working People: a Case Study of Sai Mai District, Bangkok - Ingkapakorn, Arparat; Bhanthumnavin, Nath (Journal of Health Science of Thailand, 2019)
The situation of current population indicated that the birth rate was decreasing whereas the elderly population was with increasing trend. Such change in population structure might cause many undesirable effects in the society; and efforts to mitigate the problems should be considered. The objective of this study was to assess the factors that might influence the transition toward elderly among working people. It was conducted in Sai Mai District of Bangkok. The study samples were 188 persons aged between 30-40 years old, selected by convenience sampling. Data were collected by questionnaire and analyzed by stepwise multiple linear regression. Reliability testing was performed by using KR-20 and Cronbach’s alpha coefficient. Statistical significance level was set at 0.05. It was found that there were 18 independent variables that were associated with the preparation for elderly in each aspect and overall. For the economic preparation, there were 6 independent variables which included future orientation (with 22.6% prediction value), level of education (31.7%), perceived policy on the preparation for elderly (36.5%), (benefits of being good health (38.7%), marital status (40.2%), and expenses (42.7%). As for the social preparation, 5 influenced variables were identified which include future orientation (28.2% prediction value), benefit of good mind (33.7%), level of education (35.6%), salary (37.6%) and perception about transform to elderly (39.5%. For health preparation there were 4 variables which included benefit of being good health (12.3% prediction value), perception of policy on the preparation for elderly (16.0%), future orientation (18.7%) and level of education (20.6%). Regarding the preparation of mind, 6 variables were identified: benefit of good mind (17.4% prediction value), perception of policy on the preparation for elderly (21.3%), financial debt (24.3%), having career (27.3%), perception about elderly’s rights (30.3%) and future orientation (32.6%). For the overall elderly preparation, 5 variables were identified including future orientation (26.7% prediction value), benefit of being good health (32.3%), perception of policy on the preparation for elderly (38.3%), level of education (42.7%) and debt (44.6%). This study concluded that the main influencing factor was the future orientation influencing the preparation for elderly of working people in each aspect and overall.